Whole body vibration therapy and cognitive functions: a systematic review - Nisha Shantakumari; Musaab Ahmed (AIMS Neuroscience, 2023)
Whole Body Vibration has been found to induce physiological changes in human subjects, improving their neuromuscular, respiratory and cardiovascular functions. Evidence from animal research prove that whole-body vibration appears to induce changes in molecular and cellular levels to alter cognitive functions in mice. There is evolving evidence for a potential value of whole body vibration in improving cognition and preventing the development of age-related cognitive disorders in humans. However, literature on the biological consequences of whole-body vibration on the human brain is scanty. If so, gathering the available evidences would help decide the possibility of designing appropriate whole-body vibration protocols to extend its application to induce neurocognitive enhancement and optimize its effects. Therefore, a systematic review of the literature was performed, consulting the ProQuest, MEDLINE and Scopus bibliographic databases, to summarize the available scientific evidence on the effects of whole-body vibration on cognitive functions in adults. Results of the review suggest that whole-body vibration therapy enhances a wide spectrum of cognitive functions in adults although there isn't enough evidence available yet to be able to design a standardized protocol to achieve optimum cognitive enhancement.